Diodia kuntzei k. Schum (rubiaceae, spermacoceae): A new record for the state of Acre, Brazil - de Souza, Maria Cristina (2020)
Diodia kuntzei (Rubiaceae, Spermacoceae) is prostrate herb, rooting at the nodes, with reddish stems, multifimbriate stipules, axillary one-two-flowered inflorescences, corolla with filiform tube, and indehiscent fruit. The species is recorded for the first time for the state of Acre, where it was found in Alto Juruá region, municipality of Cruzeiro do Sul, in waterlogged habitat (07°33′32″S, 072°42′59″W). Images of the plant and comments on its habitat and distribution are provided.